Intramuscular Transplantation of Human Postnatal Myoblasts Generates Functional Donor-Derived Satellite Cells - Skuk, Daniel (Nature Publishing Group, 2010)
Myogenic cell transplantation is an experimental approach for the treatment of myopathies. In this approach, transplanted cells need to fuse with pre-existing myofibers, form new myofibers, and generate new muscle precursor cells (MPCs). The last property was fully reported following myoblast transplantation in mice but remains poorly studied with human myoblasts. In this study, we provide evidence that the intramuscular transplantation of postnatal human myoblasts in immunodeficient mice generates donor-derived MPCs and specifically donor-derived satellite cells. In a first experiment, cells isolated from mouse muscles 1 month after the transplantation of human myoblasts proliferated in vitro as human myoblasts. These cells were retransplanted in mice and formed myofibers expressing human dystrophin. In a second experiment, we observed that inducing muscle regeneration 2 months following transplantation of human myoblasts led to myofiber regeneration by human-derived MPCs. In a third experiment, we detected by immunohistochemistry abundant human-derived satellite cells in mouse muscles 1 month after transplantation of postnatal human myoblasts. These human-derived satellite cells may correspond totally or partially to the human-derived MPCs evidenced in the first two experiments. Finally, we present evidence that donor-derived satellite cells may be produced in patients that received myoblast transplantation.